Production Development : Layout Project at Lundqvist Trävaru AB - Berglund, Andreas (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2019)
The purpose of the master thesis has been to examine the production system at the company Lundqvist Trävaru AB and use the gathered information to create a layout suggestion together with a couple of improvement ideas. The thesis is the final part of the Industrial Design Engineering programme at Luleå University of Technology (LTU). Lundqvist Trävaru AB is a manufacturing company that specializes in producing prefabricated building kits out of wood, but the insufficient size of their current factory located in the industrial area of Öjebyn on the outskirts of Piteå, have created a need to relocate to alarger site. This new site is located at Haraholmen south of Piteå. The aim and objective have therefore been to develop a layout suggestion as well as a couple of improvement ideas, with the purpose of solving the identified problems at the current factory, thereby making sure that they do not reappear at the new site. Methods in the form of interviews, observations and documentation reviews were performed to identify potential problems with the production system and the work organization. To aid the investigation of the current factory, literature reviews of scientific books and articles were also performed during the project, with the purpose of giving the thesis a solid scientific foundation. After an overview of the production system had been created, the next step was to analyze the identified problems. These affected many different aspects of the company, for instance the material handling, work organization, flow ofinformation, production flexibility, inventory capacity and production flow. The main problem that in turn caused many of the identified problems was the insufficient inventory capacity, which led to problems with overflowing inventories and long delivery times for materials. This in turn affected thematerial handling negatively and made it hard to keep track of materials in the factory. Additional problems that were identified was divided workstations, scattered areas for material storage, an ...